Genetic diversity and reproductive biology of the dioecious and epiphytic bromeliad Aechmea mariae-reginae (Bromeliaceae) in Costa Rica: implications for its conservation - Cascante Marín, Alfredo (2019)
Ecological traits and pollination mode associated with dioecious sexual expression in plants are likely to influence their reproductive success and levels of genetic diversity. Dioecy is an uncommon condition in Bromeliaceae. Currently, there is limited information on the reproductive ecology and genetics of dioecious and epiphytic bromeliads. Therefore, we studied the reproductive biology and genetic diversity of the epiphytic and dioecious bromeliad Aechmea mariaereginae in Costa Rica. Flowering of pistillate and staminate plants in one population showed high synchrony and were pollinated by non-hermit hummingbirds. Sex ratio was biased to males (3.5:1). Fruit set was relatively high (68%) but there was high female reproductive variance (C. V. = 59.7%). The species is capable of parthenocarpic fruit production. Using eight nuclear microsatellite markers and six populations, we found moderate to high levels of genetic variation (HE = 0.571–0.726). Populations showed significant genetic structure (G'ST = 0.385) and Bayesian population assignment grouped them into lowland and montane clusters. Isolated montane populations had slightly lower genetic diversity probably due to lower effective population size caused by biased sex ratios and recent habitat fragmentation that limits long-distance pollinator movements and results in isolation by distance. If habitat fragmentation and isolation persist, populations in montane habitats may be at higher risk of decline and extinction